Eugenol, a Plant Volatile, Synergizes the Effect of the Thrips Attractant, Ethyl Iso-Nicotinate. Issue 6 (19th October 2018) - Binyameen, Muhammad; Ejaz, Masood; Shad, Sarfraz Ali; Razaq, Muhammad; Shah, Rizwan Mustafa; Schlyter, Fredrik
Abstract: The onion thrips, Thrips tabaci Lindeman (Thysanoptera: Thripidae), is a polyphagous pest that causes serious damage to agricultural crops, vegetables, and ornamental plants worldwide. Farmers rely on the extensive usage of synthetic chemical insecticides to control T. tabaci . There is a dire need to develop alternative control strategies to overcome the problems posed by chemical insecticides. Efficient traps would allow sensitive monitoring and possibly mass trapping. A field experiment was conducted to evaluate the potential of three plant compounds with known release rates (ranging from 6–30 mg/d); eugenol (Eug), 1, 8-cineole (eucalyptol), and linalool in all possible combinations with a thrips attractant, ethyl iso-nicotinate (EI). A combination of EI with Eug increased the effect of EI by attracting 100% more thrips (effect size, 1.95) as compared to the control of EI alone. Catches in remaining treatments were lower and or not significantly different from EI alone. The results from our study could be used to develop improved volatile blends to be used for monitoring traps. Our data suggests that these traps could be effective even at very low populations.